Central domain deletions affect the SAXS solution structure and function of Yeast Hsp40 proteins Sis1 and Ydj1 - Silva, Julio C (BioMed Central, 2011)
BACKGROUND: Ydj1 and Sis1 are structurally and functionally distinct Hsp40 proteins of the yeast cytosol. Sis1 is an essential gene whereas the ydj1 gene is essential for growth at elevated temperatures and cannot complement sis1 gene deletion. Truncated polypeptides capable of complementing the sis1 gene deletion comprise the J-domain of either Sis1 or Ydj1 connected to the G/F region of Sis1 (but not Ydj1). Sis1 mutants in which the G/F was deleted but G/M maintained were capable of complementing the sis1 gene deletion. RESULTS: To investigate the relevance of central domains on the structure and function of Ydj1 and Sis1 we prepared Sis1 constructs deleting specific domains. The mutants had decreased affinity for heated luciferase but were equally capable of stimulating ATPase activity of Hsp70. Detailed low resolution structures were obtained and the overall flexibility of Hsp40 and its mutants were assessed using SAXS methods. Deletion of either the G/M or the G/M plus CTDI domains had little impact on the quaternary structure of Sis1 analyzed by the SAXS technique. However, deletion of the ZFLR-CTDI changed the relative position of the J-domains in Ydj1 in such a way that they ended up resembling that of Sis1. The results revealed that the G/F and G/M regions are not the only flexible domains. All model structures exhibit a common clamp-like conformation. CONCLUSIONS: Our results suggest that the central domains, previously appointed as important features for substrate binding, are also relevant keeping the J-domains in their specific relative positions. The clamp-like architecture observed seems also to be favorable to the interactions of Hsp40 with Hsp70.